Pengembangan Media Monopoli Kearifan Lokal Palembang Untuk Pembelajaran IPAS Kelas IV SD Negeri 81 Palembang - Adelia Safitri; Inka Inka; Gesna Joti; Meisyiska Putri (JOURNAL SAINS STUDENT RESEARCH, 2025)
This research aims to develop learning media based on monopoly games that promote Palembang local wisdom in learning IPAS for grade IV elementary school students. This media is designed to answer the needs of interactive, contextual, and fun learning and strengthen students' cultural identity. The development model used is ADDIE (Analysis, Design, Development, Implementation, Evaluation). The research subjects included practitioner experts, material experts, and media experts. The validation results show that the monopoly media is very feasible to use in learning. Validation by practitioners scored 98%, material expert validation scored 87.5%, and media expert validation reached 92%, all in the very feasible category. This media was also tested through one-to-one and small group stages, which showed positive responses from students in terms of engagement, motivation, and understanding of the material. The monopoly game proved effective in increasing students' active participation and facilitating the delivery of IPAS materials that are relevant to local values. These findings indicate that the Palembang local wisdom monopoly learning media has the potential to be an innovative alternative in the learning process in elementary schools, as well as contributing to contextualized and sustainable learning